2020
DOI: 10.20471/acc.2020.59.04.06
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Depression in Patients with Schizophrenia

Abstract: The aim of this study was to analyze risk factors present in schizophrenic patients with depressive symptomatology. The sample comprised of 76 respondents diagnosed with schizophrenia. In the study, we used the Positive and Negative Syndrome Scale (PANSS) and Calgary Depression Scale for Schizophrenia. The prevalence of depression was estimated to be 30%. The mean scores on the negative subscale of the PANSS were significantly higher in patients with schizophrenia and depression compared to control group (U=3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Previous studies in patients with schizophrenia found that baseline depression severity was negatively correlated with remission after treatment for 1 year 57 and that alleviation of depressive symptoms increased the likelihood of remission 27 , consistent with our findings. Patients with first-episode psychosis and co-occurring depression have poorer treatment outcomes (e.g., more severe symptoms, longer hospitalization, poorer functioning and quality of life, lower remission rates, and a higher risk of psychotic relapse and suicide) than patients without depression 58 60 . Depressive symptoms correlate with positive and negative symptoms in patients with first-episode psychosis 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with schizophrenia found that baseline depression severity was negatively correlated with remission after treatment for 1 year 57 and that alleviation of depressive symptoms increased the likelihood of remission 27 , consistent with our findings. Patients with first-episode psychosis and co-occurring depression have poorer treatment outcomes (e.g., more severe symptoms, longer hospitalization, poorer functioning and quality of life, lower remission rates, and a higher risk of psychotic relapse and suicide) than patients without depression 58 60 . Depressive symptoms correlate with positive and negative symptoms in patients with first-episode psychosis 61 .…”
Section: Discussionmentioning
confidence: 99%
“…And also, the study of Balci et al 16 found prevalence of some medical diseases like hypertension, chronic obstructive pulmonary disease, and coronary artery disease, was more than twice bigger in depressed schizophrenic patients. In a study by Sari et al 17 found depression rate in schizophrenia is found as 42.5%.…”
Section: Acknowledgmentsmentioning
confidence: 94%
“…Comorbid depression in schizophrenia is found to be more prevalent in middle-income compared to high-income countries [ 2 ]. This can be explained by the fact that risk factors for comorbid depression in schizophrenia, such as trauma, social adversity, and medical conditions [ 8 , 30 ], occur highly frequently in Low-Middle-Income Countries (such as the Arab Middle East and North Africa region [ 31 – 33 ]). For instance, studies found prevalence rates of depression in patients with schizophrenia of 25.6% in Saudi Arabia [ 34 ], 30% in Egypt [ 35 ], 36.3% in Qatar [ 34 ].…”
Section: Introductionmentioning
confidence: 99%